Does Parental Academic Support Consistently Predict Pupils’ Academic Achievement? Unbundling the Impacts of the Dimensions of Parental Academic Support - Emmanuel Chibuike Nwune; Charles Amaechi Anidi; Nnaemeka Kenechi Oguezue; Kingsley Chinaza Nwosu (Journal of Research in Education and Pedagogy, 2026)
The significance of parental academic support has been noted in educational research, highlighting its impact on several aspects of learning outcomes. Most researchers conceptualized parental academic support as multidimensional, given that it encompasses various strategies and activities parents adopt to support the learning of their children. Yet, few studies have unbundled the impacts of these dimensions on pupils’ academic achievement. We designed this study by employing a predictive correlational research design to determine how parental academic support predicts pupils’ academic achievement by unbundling how the various dimensions of this support impact their achievement using hierarchical multiple regression analysis. A simple random sampling method was employed to select 261 students (54% male and 46% female; mean age = 10.51 ± 1.41 years) from six intact classes across two primary schools affiliated with and administered by two tertiary institutions in Anambra State, Nigeria. We adopted the Perceived Parental Academic Support Scale developed by Chen (2005) to obtain pupils’ views regarding the academic support they receive from their parents. The scale was divided into five dimensions (interpersonal, cognitive, emotional, behavioural, and instrumental) and rated on a 4-point rating continuum from ‘strongly agree’ to ‘strongly disagree’. The average scores of the pupils for the 2023/2024 academic session were used to represent their academic achievement. Major findings indicated that pupils’ age and gender predicted their academic achievement. Also, the findings show that the cognitive dimension of parental academic support predicted the pupils’ academic achievement. We concluded from the findings of the study that pupils’ age, gender, and the cognitive dimension of parental academic support are critical to pupils’ academic achievement.